Design of an Intelligent Answering System Through Agent Based Search Engine Using Grid Technology - Jayalatchumy, D.; Kadhirvelu, D.; Ramkumar, P. (2008 First International Conference on Emerging Trends in Engineering and Technology, 2008)
Agent technology is a software entity with self-adaptation and intelligence that can accomplish a task by means of initiative service on behalf of users. The purpose of this paper is to formulate a functional architecture that supports the e-learning objectives: study individually and cooperatively, anytime and anywhere, guide specific individuals to their most relevant community. In order to make the work more efficient and to improve the performance an answering system is designed that does an intelligent search using algorithms like full text based search, word segmentation and fuzzy search. It displays the result by analyzing the userpsilas profile, experience and users needs so that the he is fully satisfied. It is made possible using case base reasoning (CBR) technique. A decentralized search engine is also built on top of grid technology with the help of software agents that allows the user to search through heterogeneous resources stored in geographically distributed digital collections.